Improving training in creativity as a background to entrepreneurship. An assessment experience at the University of Cantabria. - Ignacio Haya Salmón; Adelina Calvo Salvador; Mª Concepción López Fernández; Ana María Serrano Bedia (Universitat Politècnica de València, 2013)
This article shows a piece of research designed to assess a transversal course at the University of Cantabria (Spain). This course aims to stimulate creativity and innovation as a background to entrepreneurship. This is a course for all students in the first year of their degree and so far it has been developed over two academic years (2010-11 and 2011-12). The main results of the assessment process, which was carried out collecting both lecturers' and students' points of view, were obtained from a study based on interviews and a focus group. The assessment has enabled us to know the strengths and weaknesses of the training proposal. Furthermore, it has been useful to organize reflection on several dilemmas that arise from the analysis of data related to five categories: choice of transversal courses , activities and learning and teaching methods, classroom atmosphere and participation, assessment and improvement. This work is the first step towards a plan to evaluate courses related to entrepreneurship which are being developed at the University of Cantabria, that is to say, it is a plan to establish the status of the issue of training for entrepreneurship in this institution. The results show the potential of this type of training in the whole university and not only in studies related to the fields of economy and business.